2012
DOI: 10.1080/09658211.2012.702773
|View full text |Cite
|
Sign up to set email alerts
|

Accurate, inaccurate and omitted details in collective emotional memories: The case of Itzhak Rabin's assassination

Abstract: Collective memory of the assassination of the former Israeli Prime Minister, Itzhak Rabin, was originally examined by asking 61 Israeli students, about two weeks after the assassination (T1) and about 11 months later (T2) to fill out an open-ended questionnaire about the assassination. About 13 years later (T3) a new sample of 80 students also filled out the memory questionnaire. In T2 and T3 the participants also self-assessed various emotional and cognitive variables about their memories. All answers were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Researchers have found that Kennedy’s death shocked the American public, with many citizens feeling depressed following his murder (Ebel-Lam et al , 2010; Freedman, 1984). Similarly, researchers found that the 1995 assassination of Israeli Prime Minister Yitzhak Rabin traumatized the Israeli population (Klingman, 2001; Zelig and Nachson, 2012).…”
Section: Assassination Backgroundmentioning
confidence: 99%
“…Researchers have found that Kennedy’s death shocked the American public, with many citizens feeling depressed following his murder (Ebel-Lam et al , 2010; Freedman, 1984). Similarly, researchers found that the 1995 assassination of Israeli Prime Minister Yitzhak Rabin traumatized the Israeli population (Klingman, 2001; Zelig and Nachson, 2012).…”
Section: Assassination Backgroundmentioning
confidence: 99%